1977
DOI: 10.1037/0022-0167.24.3.231
|View full text |Cite
|
Sign up to set email alerts
|

A prescriptive approach for counselor training.

Abstract: The present study measured the effectiveness of Structured Learning Training (SLT) for teaching confrontation skills to trainees varying in conceptual development. Both a self-instruction approach and a standard implementation of SLT were effective for teaching confrontation skills. When trainees' conceptual level (CD was considered, the approaches proved differentially effective (as measured by pencil-and-paper tests). Self-instruction SLT was more effective with high CL trainees than with low CL trainees; gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Reflective listening training was more efficient than MC, but will probably be less effective with more complex communicationoriented skills. One other investigation demonstrated that "structured learning training," a package that closely parallels MC in its sequential use of instructions, modeling, discrimination training, and rehearsal with videotape feedback, is equally effective when administered through direct contact with a trainer or in a self-instructional mode (Rosenthal, 1977). Both approaches were significantly more effective than a placebo control condition.…”
Section: Micro Counseling (Mc)mentioning
confidence: 98%
See 1 more Smart Citation
“…Reflective listening training was more efficient than MC, but will probably be less effective with more complex communicationoriented skills. One other investigation demonstrated that "structured learning training," a package that closely parallels MC in its sequential use of instructions, modeling, discrimination training, and rehearsal with videotape feedback, is equally effective when administered through direct contact with a trainer or in a self-instructional mode (Rosenthal, 1977). Both approaches were significantly more effective than a placebo control condition.…”
Section: Micro Counseling (Mc)mentioning
confidence: 98%
“…Pre-training communication facilitativeness (also rated by observers from role play interviews) correlated + .33 with post-training communication facilitativeness, but added very little to the predictive power of the trainability indices. Rosenthal (1977) showed that direct contact with trainers was significantly more effective than a self-instructional approach for low "conceptual level" trainees undergoing "structured learning training." The direct contact and self-instructional approaches were equally effective with high conceptual level trainees.…”
Section: Trainee Personal Characteristics and Selectionmentioning
confidence: 98%
“…Level of conceptual complexity, one component of ego development, has also been related to empathy skills (Heck & Davis, 1973;Kimberlin & Friesen, 1977, 1980Lutwack & Hennessy, 1982;Strohmer, Biggs, Haase, & Purcell, 1983), the flexibility of counselors' verbal responses (Goldberg, 1974;Lichtenberg & Heck, 1979), and instructional (Rosenthal, 1977) and supervision approaches (Berg & Stone, 1980). In addition, Holloway and Wolleat (1980) investigated the relationship of beginning counseling students' conceptual level and prior counseling experience with their clinical assessment of a videotaped client.…”
Section: -6mentioning
confidence: 99%
“…However, of the 15 studies they examined, only 2 used counselors or trainee counselors as Downloaded by [New York University] at 02:01 15 May 2015 participants and relied on interviews as a basis for determining outcome. Of these 2 studies, 1 reported a significant positive outcome (McLachlan, 1972); the other (Rosenthal, 1977) did not. The other 13 studies used student research volunteers, or clients, or trainee teachers as participants andor did not rely on outcomes involving counseling interviews.…”
Section: Re\*iews Of Reseurch Oii CL and Counselingmentioning
confidence: 99%